Morphofunctional state of tooth tissue of rats obtained when keeping to hypercalorium diet during pregnancy. - Pysmenna, O. T.; Nikolaeva, O. V.; Naumova, O. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. It is known that the prevalence of caries among the child population of Ukraine is growing every year. Objective: study the influence of the hypercaloric diet of pregnant rats on the morphofunctional tooth state of their offspring. As part of the study, an experiment was conducted on rats of WAG/G Sto population in modeling excess weight. The material for the morphological study was the incisor tooth of the mother rats’ upper jaw, their one- and two-month offspring, studied with the help of histological and morphometric methods. Results. With the hypercaloric diet, in general, there were no signs of dyspoiesis of structural and functional components of the maxillary incisor in comparison with rats that were in the standard conditions of the vivarium. Morphological changes in mono- and bi-monthly rat offspring are of the same type in the form of discirculatory changes in the tooth pulp, dystrophic changes in odontoblast and density decrease. In the dentin, focal dystrophic changes, loci of hyper- and hypocalcinosis with ratio distortion between predentine and dentin are noted. Dystrophic changes occur in adamantoblast population, and the adamantoblast density increases. Enamel and cement are characterized by uneven mineralization, focal dystrophic changes. Moreover, two-month rats have collagenogenesis hardening in hard tissues and tooth pulp. Conclusion.It was found that with the hypercaloric diet of mothers of rats, one-and two-month offspring exhibit morphofunctional changes that may lead to the development of pathologies of hard teeth and periodontium in the future.